Campo Maior Castle's Recovery. Portugal - Sequeira, Marta (TC Cuadernos, 2022)
Commissioned by the Directorate–General for Cultural Heritage in the context of the Recovery and Enhancement Plan for the Campo Maior Castle, the aim of this project was to create the necessary safety and comfort conditions to make the castle's former gunpowder magazine – where, during archaeological excavations, remains of the old barbican were discovered – visitable. The budget for the intervention was very small. Based on this assumption, but also on the desire to promote a less intrusive – almost ephemeral – intervention, the project was conceived. In fact, li!le would be needed to make the space visitable. The new intervention consisted in the construction of a timber ramped structure in the courtyard in front of the building – allowing to overcome the difference of more than two metres between the external pavement level and the pavement level of the armoury – and in the introduction of a light and economical structure, of prefabricated tubular scaffolding – with guardrails made of solid galvanized steel bars that support metallic planks in a guardrail, commonly used in civil construction – inside the building, stabilizing a visiting circuit. The walkway formed by the scaffolding runs along the entire length of the two rooms, at the level of the old warehouse floor, allowing us not only to observe the archaeological finds, but also to understand the space as it was before its excavation. In the final section it rises, approaching the gap located at the top of the main room and offering the visitor a general perspective – of the archaeological works, of the space of the armoury, but also of the passageway itself.